Estudio de factibilidad para la creación de una fábrica de ropa deportiva en el cantón Quinsaloma, año 2014 - Duarte Moyano, Emma Daniela (2015)
This research was conducted in the Quinsaloma canton in the province of Los Rios, is reported to Quinsaloma Canton has a population of 16,476 spread over 4,573 in urban areas and 11,903 in rural areas according to the last census. The research topic is: " FEASIBILITY STUDY FOR CREATING A SPORTSWEAR FACTORY IN CANTON QUINSALOMA YEAR 2014 " , which has the overall objective; Prepare a feasibility study for setting up a factory in Sportswear Canton Quinsaloma , 2014. As specific objectives: 1) Determine using an market research survey in order to collect consumer behavior regarding the use of sportswear in Quinsaloma, 2) Conduct technical study for the establishment of a factory in Guangzhou Sportswear Quinsaloma, 3) Establish an economic survey, the initial investment and expenditure of the project and 4) determine the financial evaluation of the project leads to identify the profitability of the project The results obtained were : 48% of respondents were masculine and 52 % female gender, 42.91 % are between 26 and 35 years, 37.60 % are between 36 and 45 years, 17.49% between 16 and 25 years, 38.44 % are independent, the 33.47 % are dependents and 28 , 09% are students , 100 % of people reported not knowing the existence of a company dedicated to the manufacture and sale of sportswear, the 46.68 % reported that the frequency of purchase of garments or sportswear is annually 41.24 % semiannually make the 70.14 % of people make purchases sportswear Quevedo canton , 13.52% , the rest elsewhere. The 38.34 % prefer sports uniforms, sports uniforms followed by a 18.75%, still sporting shirts with 13.67%, the expenditure made in sportswear is 64.32 % for an average of 30 annually, the 25.21% usually spend $ 50 a year, spending the rest said $ 75 onwards the price with 43.51 %, with 40.29 % quality are the first thing that catches their attention, finally in Quinsaloma sporting events are held frequently with an 34.64 %, a rare 34.54 %. The NPV obtained for the project is 60549.86, the internal rate of return is 147.95 %, and the cost obtained for this project benefit ratio is 1.25 units, so the project is feasible Make the implementation of this project once achieved the necessary resources for financing. Producing quality and low cost.